Money Management: The Case Study of Money Behavior, Attitude, and Knowledge of Employees with Less Than Five Years of Working Experience - เบญญาศรีสวัสดิ์, ประวัฒน์ (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
This research explores the money management in terms of money behavior, attitude, and knowledge. This research focuses on the new working age people in one of state enterprise organizations in Thailand. Research objectives consist of 3 aspects, including money behavior, attitude, and knowledge. Both quantitative and qualitative research methods have been employed for this study. For the quantitative research, research questionnaire has been used to evaluate money behavior and attitude and multiple choice questions have been used to evaluate money knowledge. The specific samples are selected that they include working age people whose working experience in a state enterprise organization is less than 5 years. For the qualitative research, interview has been performed to support results obtained from the quantitative research. Research results from the quantitative research reveal that for money behavior, the sample group has been aware of security, in particular lending to other people. For money attitude, the sample group highly agrees that the key of success is come from diligent. For money knowledge, most respondents can answer 6 out of 10 questions. For further analysis, the sample group has been categorized by gender and background knowledge. The result shows that relative to females, males pay more importance to money and they feel more secure to have money. However, the sample with different education background has no difference in money behavior, money attitude and money literacy. This research suggests that different factors and sample groups used in research studies can influence research results. Results from the qualitative research can be summarized that males and females have some differences in money behavior and attitude. However, they have common opinion about that people must have an appropriate financial planning for themselves that they will have sufficient money for living in the future.